PERSEPSI MASYARAKAT DAN DAMPAK SOSIAL EKONOMI TERHADAP LAHAN BEKAS TAMBANG TIMAH SEBAGAI KAMPOENG REKLAMASI AIR JANGKANG DI DESA RIDING PANJANG KABUPATEN BANGKA - Vinda Asparita; Fournita Agustina; Yudi Sapta Pranoto (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Mining activities not only cause impacts that occur at the mine site but also the surrounding environment, so that reclamation is needed. This study aims to describe the community's perception of the existence of Kampoeng Air Jangkang Reclamation and to describe the socio-economic impact of the community on the existence of the Jangkang Water Reclamation Kampoeng. This research was conducted from September 2019 to September 2020 in Riding Panjang Village, Merawang District, Bangka Regency. The method used in this research is a survey method. Meanwhile, the sampling method used in this study was purposive sampling. The number of samples taken in this study were 93 samples from the people of Riding Panjang Village. The analytical method used is a qualitative descriptive method with a Likert scale. The results showed that the community's perception of the ex-mining land as Kampoeng Reclamation was strongly agreed with an index number of 82.4 percent covering the pre-reclamation stages, 81.4 percent covering the implementation of Kampoeng Reclamation development and an index figure of 88.8 percent covering the success of Kampoeng development. Reclamation. The social impacts that occur include positive impacts both on environmental conditions and the safety of the communities around the reclamation area. The resulting economic impact is a positive impact on people's income and employment.